The readability of the world - Blumenberg, Hans; Savage, Robert (Robert Ian); Roberts, David, 1937- (Ithaca, New York : Cornell University Press and Cornell University Library, 2022)
"Hans Blumenberg has, in the quarter-century since his death, become recognized as one of the most important philosophers of the postwar period. The Readability of the World represents Blumenberg's first full-length demonstration of the metaphorological method he had pioneered twenty years earlier in Paradigms for a Metaphorology. Whereas Blumenberg had confined himself in Paradigms to sketching this future research field, in Readability he applies his method to a single case study: the idea that the world presents itself to human beings as a book. The metaphor of the book of nature has been central to Western interpretations of reality. Beginning with ancient Greek cosmology and ending with the genetic code, Blumenberg traces the changes undergone by this metaphor in order to access the different expectations of reality that it articulates, reflects, and projects"--
A Metaphor for the Totality of Experience -- The World of Books and the Book of the World -- The Sky as Book, the Book in the Sky -- Alphabetic Analogies -- The Protracted Appearance of the Second of the Two Books -- The Illiterate Layman as Reader of the World Book -- God's Books Agree With Each Other -- Asymmetries of Readability -- Encryption and Decryption of the Human World -- World Chronicle or World Formula -- A Robinsonian World Against the Newtonian World -- Anticipations of the Nineteenth Century -- The Hamburg Book of Nature and its Reflection in KoÌ⁸nigsberg -- Signs on Foreheads, Signs in the Sky -- "How Readable the Book of Nature is Becoming . . ." -- "The World Must Be Romanticized" -- The Idea of the Absolute Book -- A Book on Nature as a Book of Nature -- The Empty World Book -- Preparation for the Interpretation of Dreams -- Making Dreams Readable -- The Genetic Code and its Readers.
"Originally published under the title Die Lesbarkeit der Welt, by Hans Blumenberg. ©Suhrkamp Verlag Frankfurt am Main 1981"--Title page verso.
Includes bibliographical references and indexes.
Translated from the German.
Description based on online resource; title from digital title page (viewed on December 07, 2022).
JSTOR
Keywords: Science -- Philosophy; Philosophy of nature; Philosophie de la nature; LITERARY CRITICISM / European / German; Philosophy of nature; Science -- Philosophy; Philosophy: metaphysics & ontology; Philosophy